2008
DOI: 10.1186/1755-8794-1-55
|View full text |Cite
|
Sign up to set email alerts
|

Pathways affected by asbestos exposure in normal and tumour tissue of lung cancer patients

Abstract: Background: Studies on asbestos-induced tumourigenesis have indicated the role of, e.g., reactive oxygen/nitrogen species, mitochondria, as well as NF-κB and MAPK signalling pathways. The exact molecular mechanisms contributing to asbestosmediated carcinogenesis are, however, still to be characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…develop their genotoxicity due to direct and indirect (inflammatory driven) molecular mechanisms (18,19,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…develop their genotoxicity due to direct and indirect (inflammatory driven) molecular mechanisms (18,19,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Not only have models of gene profiling been developed in rodents as a means of classifying the toxicity of compounds to liver and other organs (Steiner et al 2004), but this concept has previously been applied to define early molecular events following exposure of normal human bronchial epithelial cells (NHBEs) (Belitskaya-Levy et al 2007), murine nontransformed alveolar type II epithelial (C10) cells (Ramos-Nino et al 2003), human lung adenocarcinoma (A549) cells (Hevel et al 2008; Nymark et al 2007), SV40-transformed bronchial epithelial (Beas-2B) cells, and SV40-immortalized pleural mesothelial (MET5A) cells (Nymark et al 2007) to asbestos. Transcript profiling has also been used to identify differentially regulated pathways in lung and tumor tissues of asbestos-exposed and non-exposed lung cancer patients (Ruosaari et al 2008), as well as to examine gene changes in human pulmonary artery endothelial cells (HPAEC) exposed to ultrafine particles (Karoly et al 2007). A summary of results from several of these in vitro studies using asbestos can be found in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Nymark et al, (2008), provides an excellent overview of the many molecular and genetic changes in asbestos-related lung cancer. In a comparison of matched normal and lung tumor tissue, Ruosaari et al, (2008) have identified several functional pathways significantly different between asbestosexposed and nonexposed lung cancer patients including ion transport, NF-jB signaling, DNA repair, and spliceosome and nucleosome complexes. Furthermore, many pathways downregulated in asbestos-exposed subjects were related to protein ubiquination, involved in multiple cell processes, including cell cycling, apoptosis, and DNA repair.…”
Section: Discussionmentioning
confidence: 99%